Spatial database for residential property : customers' and developers' requirement / Ramizah Kamsi - Kamsi, Ramizah (2005)
This research is about the customers' and developers' requirement on the residential property for the spatial database for residential property. There are the factors that influence the customers' and developers' requirement. The objectives of the research are to identify the customers' requirement on residential property and to identify the developers' requirement on the residential properly. The research began by designing the questionnaires derived from the literature reading and colleagues' discussion. 40 respondents from the customers whose 20 from Seksyen 7 and the others are resident in Seksyen 24 and 3 respondents from developers involved in developing the residential property in Seksyen 7 and Seksyen 24. The survey conducted on the mid of October and finish by mid of November. The data that had been collected were analyzed using SPSS 11.5. The data is analyzed in order to identify the respondents' requirement and Entity Relationship Diagram has been designed. The findings are there a significant relationship between incomes of the customers with the category of residential property. The customers' and developers' requirement are also compared in this research.